2006
DOI: 10.2165/00003088-200645030-00001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacology of Cilomilast

Abstract: Chronic obstructive pulmonary disease (COPD) is a multicomponent, chronic inflammatory disease of the lungs with systemic complications. The majority of the inflammation occurs in the peripheral airways and lung parenchyma. It is a progressive disease, leading to disability and eventual death, despite conventional therapy. Inflammatory activity can be reduced by increasing intracellular cyclic adenosine-3',5'-monophosphate (cAMP) through inhibition of phosphodiesterase (PDE) IV, the principal PDE isoenzyme wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…The previous study [ 22 ] also demonstrated the lack of inhibition by cilomilast on LPS-induced cytokines. Due to the higher binding to plasma proteins (99.4%), cilomilast distributes minimally into the peripheral organs with a small volume of distribution [ 23 ]. This could lead to limited delivery to the target organs, thereby lessening the degree of therapeutic activity exhibited.…”
Section: Discussionmentioning
confidence: 99%
“…The previous study [ 22 ] also demonstrated the lack of inhibition by cilomilast on LPS-induced cytokines. Due to the higher binding to plasma proteins (99.4%), cilomilast distributes minimally into the peripheral organs with a small volume of distribution [ 23 ]. This could lead to limited delivery to the target organs, thereby lessening the degree of therapeutic activity exhibited.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical results from the six Phase III trials performed using Daxas will be reviewed below. Before, touting the benefits of PDE4 inhibitors in COPD, it is important to note that Daxas is not without its adverse events which include diarrhea, weight loss, nausea, headache and abdominal pain (Giembycz &Field 2010), which have been observed previously with other PDE4 inhibitor drugs (Down et al 2006).…”
Section: Phosphodiesterases As Targets For Copdmentioning
confidence: 98%
“…No significant metabolism-based interactions have been reported on studies with two other PDE-4 inhibitors: cilomilast (Down et al, 2006) and MK-0873 (Boot et al, 2008). Methylxanthines.…”
Section: Metabolism-based Interactions Involving Drugs Used To Treat mentioning
confidence: 99%